2017
DOI: 10.1111/jocn.13667
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ self‐perceived burden, caregivers’ burden and quality of life for amyotrophic lateral sclerosis patients: a cross‐sectional study

Abstract: Our study suggests that paying more attention to female amyotrophic lateral sclerosis patients might benefit patients in China or other South-East Asian countries under the Confucian concept of ethics. There is an urgent demand to expand medical insurance coverage to cover amyotrophic lateral sclerosis in China and other developing countries. Long and adequate supports are needed for relieving caregiver's burden. To improve the quality of life of patients, relieving the patients' SBP and caregivers' burden is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 61 publications
3
28
1
Order By: Relevance
“…These two additional factors can be interpreted similarly to the ECOG: Patients in rehabilitation phases C and B suffer from a more serious illness with decreased functionality compared to phase D and “overburdening of family” also indicates patients' health deterioration. It is well known that as patients' health condition worsens, family caregivers physically and psychologically reach their limits ( 49 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…These two additional factors can be interpreted similarly to the ECOG: Patients in rehabilitation phases C and B suffer from a more serious illness with decreased functionality compared to phase D and “overburdening of family” also indicates patients' health deterioration. It is well known that as patients' health condition worsens, family caregivers physically and psychologically reach their limits ( 49 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are at the front lines of patient care and are therefore ideally suited for this task. Patients with chronic neurological conditions may verbalize that they view themselves as burdens and verbalize strained interpersonal relationships . A sense of powerlessness is not uncommon in patients with chronic illness .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic neurological conditions may verbalize that they view themselves as burdens and verbalize strained interpersonal relationships. 1,2 A sense of powerlessness is not uncommon in patients with chronic illness. 3 In recent years, motivational interviewing (MI) techniques have been used by nurses working in a variety of clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Major research studies have shown that self-perceived burden (SPB) is experienced by certain groups of patients; e.g. chronic diseases patients [26], terminal cancer patients [27], and stroke victims [28] who experienced physical symptoms (e.g., pain and physical weakness) and psychological difficulties (e.g., depression, anxiety, and decreased quality of life) [29]. These groups of patients to various degrees rely on family members to assist and give informal care [28].…”
mentioning
confidence: 99%
“…Relying on and being burdensome to family members, especially parents and parents-in-law, may lead women to perceive shamefulness, significant guilt, and psychological burden. It has been demonstrated that in China, female patients generally tended to have a higher SPB than male patients [26]. Therefore, researchers and practitioners should pay a special attention to female patients in counties with a family-oriented culture, especially the hospitalized pregnant women with high-risk pregnancies in China, as their mental health will affect childbirth process and outcomes, child development, and family wellbeing.…”
mentioning
confidence: 99%